2008 IEEE Silicon Nanoelectronics Workshop 2008
DOI: 10.1109/snw.2008.5418473
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of TiN gate FinFET SRAM with (111)-oriented sidewall channels

Abstract: liN gate FinFETSRAMhalf-cells withdifferent J3-ratios from 1-3 have successfully been fabricated by usingthe orientation dependent wetetching andconventional reactive sputtering, forthefirst time. It is experimentally foundthatstaticmise margin (SNM)atreadcondition increases with increasing J3-ratio due to the strength of pull-down transistor. Toovercome SRAM cellsize increment withincreasing p, a fin-height controlled pass-gate (PG)SRAMstructure isproposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…[110]-oriented wafers are commercially available and have already been adopted for fin field effect transistors (finFET) in CMOS technology (Liu et al, 2008 Figure 1B. Using this arrangement and etching process, we demonstrated waveguides with propagation loss of 0.85 dB for TE polarization and 1.08 dB for TM polarization at telecomm wavelength.…”
Section: Fabrication By Anisotropic Wet Etchingmentioning
confidence: 99%
“…[110]-oriented wafers are commercially available and have already been adopted for fin field effect transistors (finFET) in CMOS technology (Liu et al, 2008 Figure 1B. Using this arrangement and etching process, we demonstrated waveguides with propagation loss of 0.85 dB for TE polarization and 1.08 dB for TM polarization at telecomm wavelength.…”
Section: Fabrication By Anisotropic Wet Etchingmentioning
confidence: 99%
“…A high static noise margin (SNM) of 203 mV is obtained owing to the strength of the pull-down transistor. 31) A PVD-TiN gate FinFET-based full-cell SRAM is being developed and will be reported elsewhere.…”
Section: Electrical Characteristics Of Finfets and Discussionmentioning
confidence: 99%
“…To investigate the nitrogen gas flow ratio, R N = N 2 /(Ar + N 2 ), dependence on the sputtered TiN gate work function (33) and its effect on the V th of FinFET (34), TiN gated MOS capacitors and FinFET CMOS inverters were fabricated by changing the R N form 17 to 100 %. The fabrication processes are basically similar to those as mentioned above.…”
Section: Device Fabricationmentioning
confidence: 99%
“…However, there have been no systematical studies regarding the PVD TiN gate work function control using the nitrogen gas flow ratio, R N = N 2 /(Ar + N 2 ), in the sputtering. In order to clarify the R N dependence of TiN work function and its effect on the device characteristics, at first, we fabricated TiN gate MOS capacitors and bulk-planar MOSFETs (33). It was experimentally found that the more R N offers a slightly lower work function due to the higher nitrogen concentration in the TiN film with increasing the R N .…”
Section: Ecs Transactions 13 (2) 239-252 (2008)mentioning
confidence: 99%